Human Capital Management Information System at the Nelson Mandela African Institution of Science and Technology of Tanzania: Challenges Encountered - Marcel, Nicodemus S; Tefurukwa, Oscar W (UI Scholars Hub, 2023)
In 2011, government institutions began utilizing HCMIS to reduce the manual workload of traditional administrative processes. The adoption of HCMIS in Tanzania is expected to increase efficiency by optimizing data accuracy, reducing costs, and eliminating paperwork. However, payroll losses continue to persist in the public sector. In 2018, the government incurred losses of Tanzania shillings (Tshs) 19.6 billion to 12,697 ghost workers. This study examines the challenges hindering the application of HCMIS in supporting selected human resource management (HRM) functions at the Nelson Mandela African Institution of Science and Technology (NM-AIST). This study applied Institutional Theory and Socio-Technical Theory as its analytical framework, gathering primary data through interviews with 16 respondents and reviewing reports for secondary data. Content analysis was employed for both primary and secondary data. The findings indicate several barriers to the effective utilization of HCMIS for HRM functions at NM-AIST, including inadequate Information and communications technology (ICT) expertise among system users, power interruptions, instability of internet connectivity, insufficient integration with other government systems, limited support for certain HRM functions, unsatisfactory employee self-service, financial constraints, and lack of top management support. To address these issues, the study recommends frequent training for HCMIS users as well as the allocation and timely disbursement of adequate budget for HCMIS to improve all HRM functions in public higher learning institutions in Tanzania.